Progress on Women’s Equality within UK and Canadian Trade Unions: Do Women’s Structures Make a Difference? - Parker, Jane; Foley, Janice (Relations industrielles / Industrial Relations, 2010)
Many Canadian and UK trade unions host collective structures for women unionists. These structures continue to widen in form to encompass women’s conferences, committees, courses, meetings, seminars, workshops, caucuses, branches and networks. The bulk of extant work on union women’s structures focuses on their concern with improving women’s conditions in the workplace. However, a growing body of works acknowledges their role as agents for change within the union setting in promoting women’s equality and in supporting union revitalization efforts.This study focuses on women’s structures’ meaning for progress with women’s equality within UK and Canadian unions. Using national surveys and semi-structured interview evidence supplied by a wide variety of unionists, it “maps” and cross-nationally compares equality achievements for women in this setting. The assessment is structured by a typology of union dimensions where progress on women’s equality has been emphasized in the literature: i) union membership and participation, ii) union education/training, iii) local union position-holding, iv) convention attendance and v) union leadership. Thematic and simple quantitative analyses were employed to account for the nature of progress in these areas for women in relation to women’s structures’ presence and activity.It emerges that the dimensions for women’s union involvement are interrelated, and that women’s union involvement to date has not been comprehensively gauged, particularly in terms of its parity with men’s activity and empowerment in unions, and also with regard to the influences on the level and character of advances towards union equality for women. Further, women’s structures are shown to play a part in effecting uneven progress for women on additional equality indices that emerge from the data, ranging from more inclusive language in union constitutions through new union ways of working to union action on interests which reflect gendered structural inequalities in that setting. According to the informants, the uneven character of women’s union equality advancements reflects the varying obduracy of impediments to women’s structures’ equality goals and the ambition of their equality initiatives.The article’s concluding discussion centres on the significance of equality developments in UK and Canadian unions for progressing institutional goals (e.g., union membership growth, strong identity, internal cohesion, diverse interest representation) and for refining assessments of women’s advancement towards equality in unions. Further, it emphasizes the need for women’s structures, advancements as internal union critics and guardians of existing women’s equality achievements, to profile their “contribution” to union equality. Efforts to develop an expanded repertoire of internal equality measures might also encourage UK and Canadian unions themselves to re-evaluate the fullness of conventional measures of their influence, given continuous pressure on union strategists to find a solid and innovative basis for union revitalization.